Answer:
c = 64
Step-by-step explanation:
(a-b)² = a² - 2ab + b²
h²- 16h + c
So, 2ab = 16h
2 * h * b = 16h {as a =h}
b= 16h / 2h
b = 8
c = b² = 8*8 = 64
Answer:
![\large\boxed{5x-6y=16}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B5x-6y%3D16%7D)
Step-by-step explanation:
The standard form of an equation of a line:
![Ax+By=C](https://tex.z-dn.net/?f=Ax%2BBy%3DC)
We have the equation in the point-slope form. Convert:
![y+1=\dfrac{5}{6}(x-2)\qquad\text{multiply both sides by 6}\\\\6y+6=6\!\!\!\!\diagup^1\cdot\dfrac{5}{6\!\!\!\!\diagup_1}(x-2)\\\\6y+6=5(x-2)\qquad\text{use the distributive property}\\\\6y+6=(5)(x)+(5)(-2)\\\\6y+6=5x-10\qquad\text{subtract 6 from both sides}\\\\6y+6-6=5x-10-6\\\\6y=5x-16\qquad\text{subtract}\ 5x\ \text{from both sides}\\\\-5x+6y=5x-5x-16\\\\-5x+6y=-16\qquad\text{change the signs}\\\\\boxed{5x-6y=16}](https://tex.z-dn.net/?f=y%2B1%3D%5Cdfrac%7B5%7D%7B6%7D%28x-2%29%5Cqquad%5Ctext%7Bmultiply%20both%20sides%20by%206%7D%5C%5C%5C%5C6y%2B6%3D6%5C%21%5C%21%5C%21%5C%21%5Cdiagup%5E1%5Ccdot%5Cdfrac%7B5%7D%7B6%5C%21%5C%21%5C%21%5C%21%5Cdiagup_1%7D%28x-2%29%5C%5C%5C%5C6y%2B6%3D5%28x-2%29%5Cqquad%5Ctext%7Buse%20the%20distributive%20property%7D%5C%5C%5C%5C6y%2B6%3D%285%29%28x%29%2B%285%29%28-2%29%5C%5C%5C%5C6y%2B6%3D5x-10%5Cqquad%5Ctext%7Bsubtract%206%20from%20both%20sides%7D%5C%5C%5C%5C6y%2B6-6%3D5x-10-6%5C%5C%5C%5C6y%3D5x-16%5Cqquad%5Ctext%7Bsubtract%7D%5C%205x%5C%20%5Ctext%7Bfrom%20both%20sides%7D%5C%5C%5C%5C-5x%2B6y%3D5x-5x-16%5C%5C%5C%5C-5x%2B6y%3D-16%5Cqquad%5Ctext%7Bchange%20the%20signs%7D%5C%5C%5C%5C%5Cboxed%7B5x-6y%3D16%7D)
Answer:
y = 1 1/9
BRO MAKE ME THE BRAINLIEST PLS
If the ratio is 14 childen to every 5 teachers, and there are thirty teachers... there are 84 children. hope I could help!
Answer:
a. f(-1)=12
b. f(2t)=16t²-6t+5
c. f(t-2)=4t²-19t+27
Step-by-step explanation:
For a, b, c, we are given an input. We plug that into f(x) to find our answers.
a. f(-1)=12
f(-1)=4(-1)²-3(-1)+5
f(-1)=4+3+5
f(-1)=12
-------------------------------------------------------------------------------------------------------------
b. f(2t)=16t²-6t+5
f(2t)=4(2t)²-3(2t)+5
f(2t)=4(4t²)-6t+5
f(2t)=16t²-6t+5
-------------------------------------------------------------------------------------------------------------
c. f(t-2)=4t²-19t+27
f(t-2)=4(t-2)²-3(t-2)+5
f(t-2)=4(t²-4t+4)-3t+6+5
f(t-2)=4t²-16t+16-3t+6+5
f(t-2)=4t²-19t+27